The Existence of Sign Language Interpreters in Assisting Deaf Individuals in the Creation of Notarial Deeds - Ratna Sari, Valentania; Santoso, Budi; Jauharoh, Arini (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2024)
This study examines the crucial role of sign language interpreters in assisting deaf individuals as clients. This study reveals a disparity in the Indonesian legal system when it comes to providing support for individuals with hearing impairments (deaf people) compared to the comprehensive framework in the United States, which mandates accommodations through legislation such as the United Nations Convention on the Rights of Persons with Disabilities (CRPD) and the American Disabilities Act (ADA). This study uses a normative juridical approach, analyzing legal texts, and a comparative framework to identify best practices and deficiencies in the current Indonesian system. The results indicate a lack of legal provisions for sign language interpreters in Indonesia, leading to potential miscommunication and legal misunderstandings among deaf clients. The conclusion emphasizes that notaries, as public officials, are required to optimize their services to the public, reflecting an ethical and professional commitment to providing fair and equal services, even in the face of inadequate legal frameworks. Practical implications suggest that implementing these changes will not only uphold the principles of justice and equality, but also enhance the effectiveness and inclusivity of legal services for the deaf community in Indonesia.